Evaluation of signal-to-noise and distortion ratio degradation in nonlinear systems - Lavrador, P.M.
This paper presents a new figure-of-merit to evaluate signal-to-noise and distortion (S1NAD) ratio degradation in nonlinear systems, herein referred to as the noise and distortion figure (NDF). In order to obtain a mathematical formula for this NDF, the best linear approximation calculation is presented for memoryless and dynamic nonlinear systems, which can be modeled by a finite Volterra series. To the best of the authors' knowledge, this is the first time such an attempt of calculating the NDF for a nonlinear and dynamic system is made. NDF results are discussed in both types of systems by means of numerical simulations of systems up to the third order.